1977
DOI: 10.1002/j.1879-3479.1977.tb00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications in Laparoscopy

Abstract: The numberous benefits and the minimal but acknowledged risks of laparoscopy are discussed. Factors related to complications include operator experience, instrument and equipment technology, types of procedures, and anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…Yet another factor might be the experience of the surgeon. During the first part of the laparoscopic learning curve the risk of complications is greater 6,12,14,19,37 . As most papers reviewed were published in the 1990s, they may not be representative of current practice.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Yet another factor might be the experience of the surgeon. During the first part of the laparoscopic learning curve the risk of complications is greater 6,12,14,19,37 . As most papers reviewed were published in the 1990s, they may not be representative of current practice.…”
Section: Discussionmentioning
confidence: 98%
“…However, bowel perforation with delayed diagnosis is still mostly treated with a laparotomy in order to evaluate the entire abdomen 3,16 . It has been suggested that burn spots and other serosal damage should be treated immediately to avoid serious morbidity 16,32,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Phillips [10] and Deziel et al [5] have correlated the incidence of complications in the course of laparoscopy with the surgeon's experience with the particular procedure and the specific difficulties encountered during the operation. In our study, 50% of the injuries occurred at the hands of experienced surgeons who had already performed >100 laparoscopic procedures [18].…”
Section: Discussionmentioning
confidence: 99%
“…Croce et al [14] also suggest avoiding the use of sharp-pointed suction/irrigation devices to retract the duodenum. The risk of complication in the course of laparoscopic surgery is said to relate to the operator’s experience with the procedure and the difficulty of the operation [4, 7, 15, 16] but may also occur in the hands of experienced surgeons [2, 17, 18]. …”
Section: Discussionmentioning
confidence: 99%